Resource Heterogeneity, Not Resource Quantity, Plays an Important Role in Determining Tree Species Diversity in Two Species-Rich Forests - Zhang, Liwen; Mi, Xiangcheng; Harrison, Rhett D.; Yang, Bo; Man, Xingxing; Ren, Haibao; Ma, Keping (Frontiers in Ecology and Evolution, 2020)
There is still considerable debate about the relative importance of resource heterogeneity and resource quantity in the maintenance of species diversity in a community. The resource heterogeneity hypothesis proposes that spatial heterogeneity of limiting resources and inter-specific differences in resource requirements will determine species richness. In contrast, the resource quantity hypothesis predicts that average resource supply rates contribute to species richness by their effects on plant density and stochastic population dynamics. However, the evaluation of the two hypotheses in observational studies is associated with a major methodological challenge as average resource supply rate often covaries with resource heterogeneity. Using a novel approach derived from the relationships between average resource supply rate, resource heterogeneity (calculated as the standard deviation of environmental factors) and plant density in the resource hypotheses, we evaluated the relative importance of resource quantity and resource heterogeneity with a variation partitioning model in Gutianshan (GTS) forest plot, China and Barro Colorado Island (BCI) forest plot, central Panama. We found that resource quantity explained much less of the variation in species richness than resource heterogeneity in both of GTS and BCI (44.5% vs 4.9% in GTS and 20.4% vs 0.8% in BCI at the 20×20 m scale, 57.5% vs 3.4% in GTS at the 40×40 m scale and 34.5% vs 2.6% in BCI at the 50×50 m scale). We also found that resource heterogeneity governed species richness in GTS, whereas spatial processes dominated species diversity in BCI. Moreover, most of the effect of resource heterogeneity and resource quantity on species richness overlapped with that of spatial processes. This result indicates that most effects of resources could also be explained by spatial processes, such as dispersal limitation. Therefore, resource heterogeneity and spatial processes, but not resource quantity played an important role in determining species diversity in these two old-growth forests. This is in contrast to the results of several manipulative studies, which found that resource quantity governed species diversity when one or a limited number of resources were considered. This suggests that the processes determining species richness along ecological gradients are complicated and determined by the interaction of various processes.